O reconhecimento legal da filiação socioafetiva na experiência do Estado de Pernambuco . - Cintra, Graciliano de Souza (2018)
Families Law has been submitted to a process of re-signification in Post-Modernity, due mainly to the central role played by Human Rights and Human Dignity in contemporary legal systems. As a consequence of the so-called “New Law of Families”, the concept of socio-affective children comes into play in order to legally describe those child-parent relations which are entirely based on affectivity and do not trace back to any biological bond. As of the year 2013, 5 (five) Federal States began to enable socio-affective child recognition by public notaries, at the end of 2017 the Brazilian National Justice Counsel regulated the subject with the Directive 63. This work has a specific objectives the concept of socio-affective children, verifies the proportion between voluntary and litigation socio-afective parenthood recognition, identifies among the voluntary cases in which proportion does it happen via notaries offices and via litigation, and also analyses if Directive 63 can facilitate the recognition via notaries office. A qualitative research will be conducted via bibliographic review and a quantitative research collecting data from Family Courts, 2º Children and Youth Court and on Notaries of Civil Records of the Capital.